Технології організації дистанційного навчання в Україні - Голик, О. П.; Каліч, В. М.; Жесан, Р. В.; Волков, І. В.; Holyk, O.; Kalich, V.; Zhesan, R.; Volkov, I. (ЦНТУ, 2021)
В статті виконано огляд та аналіз технологій для дистанційної форми навчання в Україні, їх переваги та недоліки. Запропоновано заходи для покращення ефективності організації дистанційної форми навчання. To prevent the spread of coronavirus infection, educational institutions from time to time switch to distance learning. The article reviews the ways of organizing distance learning in Ukraine, existing technologies for distance learning, electronic resources, and educational platforms. The most common web services for online learning are considered. The advantages and disadvantages of distance learning in the conditions of classical education are determined. As a result, it was found that the disadvantages outweigh the advantages, which significantly affects the quality of education as a whole. The main disadvantages: the low level of digital literacy, insufficient control over the acquisition of knowledge, and lack of social interaction between peers. Despite these shortcomings, the organization of distance learning by the Ministry of Education and Science of Ukraine and educational institutions is performed at a sufficient level. However, this process needs to be improved in terms of privacy, data protection and digital literacy. To address the lack of proper parental control, it is proposed at the state level to provide parents with the opportunity to be present directly during their children's distance learning, while being able to maintain their jobs and wages.
Technologies for Distance Education in Ukraine
Keywords: методика; дистанційне навчання; цифрові технології; освітня платформа; онлайн-навчання; methodology; distance learning; distance education; digital technologies; educational platform; online learning